Predation, removal and seed dispersal in a wetland dominated by palms (Arecaceae). - Myers, Ronald L. (2013)
In the Tortuguero floodplains, Costa Rica, a significant number of trees such as Carapa guianensis, Pentaclethra macroloba and the palm Manicaria saccifera have floating seeds adapted to hydrocory, while others, such as the almendro Dipteryx oleifera and the raffia palm Raphia taedigera have heavy seeds that do not float. These species have differential distributions, and while C. guianensis, P. macroloba and D. oleifera also grow on slopes away from the flood, the palms M. saccifera and R. taedigera hardly occur outside the swamps, where they stand as the dominant species. To understand the differences in the micro-distribution of these tree species in waterlogged environments and differences in their seed adaptations, I did a series of experiments to compare the loss and germination of their seeds in the slope forest and in palm swamps in the region. Overall, seeds in the forest slope have higher removal rates than those in the M. saccifera and R. taedigera swamps. This last one exhibits the lowest seed loss of all three habitats. Also, differences in seed predation/removal were noticed between the two species of palms studied. Thus, seeds of M. saccifera disappeared rapidly, regardless of density aggregation and location in the swamp. Removal rates in R. taedigera seeds were low in the raffia dominated swamp, where apparently, seed losses are slightly higher in the mounds of palm clumps than in the swamp floor. These observations suggest that both: flooding and microtopography determine, directly or indirectly, the fate of tree species within these wetlands. Restrictions on seed dispersal and the slow germination confine R. taedigera marshes and flooded places, whereas flooding and predators mediate in the distribution of the other tree species.